2012
DOI: 10.1038/ajg.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Post-Infectious Irritable Bowel Syndrome and Functional Intestinal Disorders Following a Water-Borne Viral Gastroenteritis Outbreak

Abstract: Our study provides evidence that Norovirus GE leads to the development of PI-IBS in a substantial proportion of patients (13%), similar to that reported after bacterial GE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 27 publications
5
81
0
12
Order By: Relevance
“…Zanini et al [16] reported that 19% of 348 patients with irritable bowel syndrome had weight loss and that the mean weight loss was 3 kg. In a study investigating laboratory parameters and the nutritional status of 180 patients who were diagnosed with FD based on the Rome II criteria, 30 (16.67%) patients had weight loss between 5 and 10% of their initial body weight, and 8 (4.44%) had weight loss of >10% of their initial body weight [17].…”
Section: Discussionmentioning
confidence: 99%
“…Zanini et al [16] reported that 19% of 348 patients with irritable bowel syndrome had weight loss and that the mean weight loss was 3 kg. In a study investigating laboratory parameters and the nutritional status of 180 patients who were diagnosed with FD based on the Rome II criteria, 30 (16.67%) patients had weight loss between 5 and 10% of their initial body weight, and 8 (4.44%) had weight loss of >10% of their initial body weight [17].…”
Section: Discussionmentioning
confidence: 99%
“…Gemulla and Pessler reported 2 cases of possible postinfectious arthritis related to norovirus infection (72). Thirteen percent of patients who had been affected during a waterborne norovirus outbreak and who responded to a questionnaire reported symptoms consistent with irritable bowel syndrome 12 months after their infection (73).…”
Section: Figmentioning
confidence: 99%
“…Disease severity is usually moderate, but morbidity and mortality rates due to NoV infection are increasingly becoming evident, with particularly high tolls taken on children and immunocompromised and aged populations (2)(3)(4)(5)(6)(7)(8)(9), resulting in an estimated 200,000 deaths per year (10). In addition, postinfectious irritable bowel syndrome develops in a substantial portion of patients (11). These groups of people, in addition to military personnel, childcare and health care providers, and food handlers, would benefit from a NoV vaccine.…”
mentioning
confidence: 99%